Hematological and Biochemical Profiles of Patients with Dengue Virus Infection in Lalitpur, Nepal - Rai, Indira; Paudel, Subash; Shrestha, Santosh; Manandhar, Debbie; Rai, Shiba Kumar (Nepal Medical College Journal, 2024)
Dengue viral infection is a disease transmitted by mosquitoes of the Aedes genus, and it arises as a result of being bitten by mosquitoes that are carrying the virus. This infection induces a wide range of changes in the body’s immune system. Thus serological evaluation together with hematological and biochemical parameters in cases of dengue viral infection make an accurate clinical diagnosis. The main objective of this study was to study the serological, hematological, and biochemical parameters among patients infected with Dengue virus. A total of 102 blood samples were collected at Asrik Diagnostic Lab, Lalitpur during the period of August to October 2022. Samples were analyzed by following methods: hematological tests were done by coulter counter, Biochemical tests were done by fully automated analyzer and serological tests were done by ELISA. Of the 102 blood samples NS1 antigen was detected in 62 (60.9%) whereas anti-dengue IgM antibody was detected in 10 (9.8%). Leukopenia and thrombocytopenia were present in 33 (53.1%) and 32 (51.6%) of the 62 NS1 positive samples, respectively. Of the 62 cases, only 16 samples were tested for the alanine aminotransferase (ALT) and aspartate aminotransferase (AST). Out of 16 samples, ALT and AST level were significantly higher in 11 (68.8%) and 14 (87.5%) positive cases, respectively. The statistical analysis showed that there was no significant association between NS1 and IgM. It can be concluded that the investigation of leukocytes, thrombocytes, ALT, and AST helps to diagnose the dengue efficiently.